Efficacy and Safety of Different Intravenous Glucocorticoid Regimens in the Treatment of Graves’ Ophthalmopathy: A Meta-Analysis - Jing Chen; Nuo Xu; Huilan Sun; Gang Chen (Journal of Ophthalmology)
Purpose. The intravenous glucocorticoid (iv GC) represents the mainstay of therapy for Graves’ ophthalmopathy (GO), but uncertainty remains concerning the optimal regimen. Although the European Group on Graves’ Orbitopathy (EUGOGO) regimen has been commonly employed, evidence for its superiority to other regimens is still lacking. The aim of this meta-analysis was to compare the efficacy and safety of the EUGOGO regimen with higher-dose regimens in the management of GO. Methods. A systematic review and meta-analysis of randomized controlled trials (RCTs) and cohort studies comparing the EUGOGO regimen with higher-dose regimens was conducted. PubMed, Embase, and Web of Science databases were searched for relevant studies. The efficacy outcomes were response rate, change in clinical activity score (CAS), rate of proptosis improvement, and retreatment rate. The safety outcome was the incidence of adverse events. Results. In the five included eligible trials, 136 participants in the EUGOGO regimen and 177 participants in higher-dose regimens were evaluated. Compared with the EUGOGO regimen, higher-dose regimens had no beneficial effect on the response rate, change of CAS, rate of proptosis improvement, and retreatment rate (OR: 1.3; 95% CI: 0.36–4.65; SMD: –0.04; 95% CI: –0.54, 0.45; OR: 0.79; 95% CI: 0.44–1.44; OR: 0.87; 95% CI: 0.27–2.77). For the incidence of adverse events, the results also showed no significant difference between the 2 groups (OR: 1.14; 95% CI: 0.62–2.09). Conclusion. The current evidence showed that the efficacy of the EUGOGO regimen was comparable with higher-dose regimens. Since there was no significant difference in the incidence of adverse events between the two regimens, appropriate selection of patients and careful monitoring were required in both regimens. More well-designed, large-scale, and longer follow-up period studies were needed to further verify the finding of this analysis.